Evaluation of the effect of viticulture biofungicide yeasts on the seed germination and growth of lettuce seedlings (Lactuca sativa L.) in vitro. Phytotoxicity analysis - Lencinas, Marcos Gabriel; Pesce, Virginia Mercedes; Flores, Cintia Belen; Vazquez, Fabio; Nally, Maria Cristina (REVISTA TERRA LATINOAMERICANA, 2020)
Botrytis cinerea can affect lettuce under both greenhouse and f ield conditions. Vitiviniculture yeasts Saccharomyces cerevisiae and Schizosaccharomyces pombe showed activity against B. cinerea isolated from lettuce, in vitro. However, it is unknown whether these yeasts affect seed germination and/or growth of lettuce seedlings. Objective: To evaluate the effect of vitiviniculture yeasts on seed germination and growth of seedlings emerging from lettuce (L. sativa), in vitro. The yeasts were inoculated on lettuce seeds incubated in plastic trays. At 4 and 7 days, the % of germinated seeds, length of radicle, hypocotyl and cotyledons were evaluated. The vigor index (IV) (7 days) was also evaluated. Results: After 4 days, four yeasts BSchp67, BSc92, BSc121 and BSc203 signif icantly promoted the germination of lettuce seeds compared to the control. Of these yeasts, two increased the cotyledon length. At 7 days, six yeasts BSc16, BSc61, BSchp67, BSc92, BSc121 and BSc203 increased the % of germinated seeds and the hypocotyl length. At 4 and 7 days none of the yeasts assayed signif icantly increased the radicle length. The seedlings pre-inoculated with the wine yeasts presented an IV similar to the control, except the seedlings inoculated with BSc81, where the IV was smaller. Conclusions: The effect of yeasts on the lettuce germination and growth was variable. At the end of the assay, yeasts BSc5, BSc47, BSc68, BSc49, BSc56 and BSc92 did not negatively affect the germination rate, vegetative growth (radicle, hypocotyl, cotyledons), nor the vigor of the lettuce seedlings, therefore they could be used as possible biocontrol agents. The last three strains mentioned above promoted hypocotyl growth (day 7). These data suggest the possibility of using these yeasts as biofungicides and as possible plant growth promoters (dual function).